Salivary Gland Mucosa‐Associated Lymphoid Tissue–Type Lymphoma From Sjögren's Syndrome Patients in the Majority Express Rheumatoid Factors Affinity‐Selected for IgG. Issue 8 (8th July 2020) - Bende, Richard J.; Janssen, Jerry; Beentjes, Anna; Wormhoudt, Thera A. M.; Wagner, Koen; Haacke, Erlin A.; Kroese, Frans G. M.; Guikema, Jeroen E. J.; van Noesel, Carel J. M.
Abstract : Objective: Patients with Sjӧgren's syndrome (SS) have an increased risk of developing malignant B cell lymphomas, particularly mucosa‐associated lymphoid tissue (MALT)–type lymphomas. We have previously shown that a predominant proportion of patients with SS‐associated salivary gland MALT lymphoma express somatically hypermutated IgM with strong amino acid sequence homology with stereotypic rheumatoid factors (RFs). The present study was undertaken in a larger cohort of patients with SS‐associated MALT lymphoma to more firmly assess the frequency of RF reactivity and the significance of somatic IGV ‐region mutations for RF reactivity. Methods: B cell antigen receptors (BCRs) of 16 patients with SS‐associated salivary gland MALT lymphoma were analyzed. Soluble recombinant IgM was produced of 12 MALT lymphoma samples, including 1 MALT lymphoma sample that expressed an IgM antibody fitting in a novel IGHV3‐30 –encoded stereotypic IGHV subset. For 4 of the 12 IgM antibodies from MALT lymphoma samples, the somatically mutated IGHV and IGKV gene sequences were reverted to germline configurations. Their RF activity and binding affinity were determined by enzyme‐linked immunosorbent assay and surface plasmon resonance, respectively. Results: Nine (75%) of the 12 IgM antibodies identified in patients with SS‐associated salivary gland MALT lymphoma displayed strong monoreactive RF activity. Reversion of the IGHV and IGKV mutations to germline configuration resulted in RF affinities for IgG that were significantly lower for 3 of the 4 somatically mutated IgM antibodies. In stereotypic IGHV3‐7 / IGKV3‐15 –encoded RFs, a recurrent replacement mutation in the IGKV3‐15 –third complementarity‐determining region was found to play a pivotal role in the affinity for IgG‐Fc. Conclusion: A majority of patients with SS‐associated salivary gland MALT lymphoma express somatically mutated BCRs that are selected for monoreactive, high‐affinity binding of IgG‐Fc. These data underscore the notion that soluble IgG, most likely in immune complexes in inflamed tissues, is the principal autoantigen in the pathogenesis of a variety of B cell lymphomas, particularly SS‐associated MALT lymphomas.